Teaching media in studying collocation for increasing students’ language intuition - Dyah Ambar Wuryandari (LADU: Journal of Languages and Education, 2021)
Background: Teaching collocation to the students is not as easy as teaching grammar. Mastering collocation helps students to understand well the lesson given by the teachers and to use language to express their ideas properly. Purpose: This study aims to investigate to what extent text used as teaching media for studying collocation. Design and methods: A library research was done to gather information on teaching media for students that suitable for studying collocations for increasing language intuition. Results: The texts that commonly contain collocation is a newspaper feature, a film review, a website for tourists, conversations, lectures, songs, and films.